Apophatism and Cataphatism in Protestantism - Constantine PROKHOROV (Богословські роздуми: Східноєвропейський журнал богословʼя)
The author of the paper shows the essential superiority of the apophatic way of knowing God over the cataphatic way in Christian theology. Protestantism, which frequently (and often deservedly) is accused of excessive rationalism, has actually remained indifferent to this problem. The present brief research intends to show that Protestants have even more grounds (in comparison with Roman Catholics and Orthodox) to include apophatism in their common epistemological concept. Having deprived themselves intentionally of reliance on a material beginning in issues of faith, most followers of the Reformation worship the God Invisible, who cannot be portrayed. Additionally, the author of the paper puts special emphasis on the apophatic approach to the Lord’s Supper, suggesting that Russian Baptists reconsider this rite and openly style it as sacrament.